Is age discrimination a less serious form of discrimination?. (September 2019) - Goosey, Stuart
Abstract: The UK courts and the CJEU have often treated age discrimination as a less serious form of discrimination. This is reflected in the courts' reluctance to offer rigorous scrutiny when evaluating whether age-differential treatment is objectively justified under anti-discrimination law. Further, a number of judges have asserted that age discrimination must be understood as different to other forms of discrimination, such as race or sex discrimination. This paper argues that age discrimination is not fundamentally different or prima facie less serious than other forms of discrimination. Age discrimination can undermine the same principles that paradigm forms of discrimination also undermine, including: creating inequality of opportunity by disadvantaging people because of a trait that is outside a person's control; undermining social equality by creating a hierarchy of social status between different groups; violating autonomy by diminishing people's capacity to have control over their lives; and communicating disrespect by conveying that particular groups have a diminished moral or social worth. It follows, contrary to the approach of much of the case law, that the courts should offer rigorous scrutiny of age-differential treatment to identify these harms and only permit age distinctions that are strictly tailored to enhance equality or other important values.